Pitavastatin-attenuated cardiac dysfunction in mice with dilated cardiomyopathy via regulation of myocardial calcium handling proteins - Hu Wei; Jiang Wen-Bing (Acta Pharmaceutica, 2014)
C57BL/6 mice with dilated cardiomyopathy (DCM) were randomly divided to receive placebo or pitavastatin at a dose of 1 or 3 mg kg-1d-1. After 8 weeks treatment, mice with dilated cardiomyopathy developed serious cardiac dysfunction characterized by significantly enhanced left ventricular end-diastolic diameter (LVIDd), decreased left ventricular ejection fraction (LVEF) as well as left ventricular short axis fractional shortening (LVFS), accompanied with enlarged cardiomyocytes, and increased plasma levels of N-terminal pro-B type natriuretic peptide (NT-proBNP) and plasma angiotensin II (AngII) concentration. Moreover, myocardium sarcoplasmic reticulum Ca2+ pump (SERCA-2) activity was decreased. The ratio of phosphorylated phospholamban (PLB) to total PLB decreased significantly with the down-regulation of SERCA- -2a and ryanodine receptor (RyR2) expression. Pitavastatin was found to ameliorate the cardiac dysfunction in mice with dilated cardiomyopathy by reversing the changes in the ratios of phosphorylated PLB to total PLB, SERCA-2a and RyR2 via reducing the plasma AngII concentration and the expressions of myocardium angiotensin II type 1 receptor (AT1R) and protein kinase C (PKC)b2. The possible underlying mechanism might be the regulation of myocardial AT1R-PKCb2-Ca2+ handling proteins.